Analysis of regional variations in influence of household and environmental characteristics on prevalence of diarrhoea among under-five children in Nigeria (2017)
Background: Until now, factors influencing diarrhoea in children has been studied in Nigeria without full recourse to her wide geopolitical diversities. Aim: This study assessed the differentials in regional prevalence of diarrhoea and the role of household and environmental characteristics in the distribution and likelihood of diarrhoea among children under-five years within each geopolitical region in Nigeria. Subjects and Methods: A cross-sectional study among households with under-five children. We used the data from the 2012 Nigeria National HIV/AIDS and Reproductive Health Survey (NARHS Plus II). We weighed the data and used descriptive statistics, Pearson Chi-square (x2 ) and logistic regression to analyse data at 5% significance level. Results: Over a third, 38.0% (5062/13322) of households sourced drinking water from non-improved sources, highest in North East, 45.3% (1049/2315) and least in South West, 27.6% (521/1888) Over half, 52.7% (7021/13322) of toilets were non-improved, highest in North East, 68.6% (1588/2315) and least in South West, 35.7% (674/1888), most households practice open defecation. The overall prevalence of diarrhoea was 13.0% (1732/13322), 17.0% (294/1732) in North East and higher in other regions than 9.0% (156/1732) in the south west. The odds of diarrhoea was significantly higher among rural households in the South-South (OR=2.1, 95% CI: 1.4-3.1) but more prevalent in urban North East and South East. Also, the odds of having diarrhoea increased with wealth quintile to which household belongs was significant in all the regions except in the North East. Conclusions: The prevalence of diarrhoea varied widely across the regions. Also, the influence of household and environmental characteristics on the prevalence of diarrhoea differed across the geopolitical regions. This is an indication that policies on control of diarrhoea should be region-specific.